Elucidated tumorigenic role of MAML1 and TWIST1 in gastric cancer is associated with Helicobacter pylori infection. (January 2022) - Hamidi, Amir Abbas; Forghanifard, Mohammad Mahdi; Gholamin, Mehran; Moghbeli, Meysam; Memar, Bahram; Jangjoo, Ali; Motie, Mohammad Reza; Molaei, Fatemeh; Abbaszadegan, Mohammad Reza
Abstract: Background: Epithelial-mesenchymal transition (EMT) has a fundamental role in tumor initiation, progression, and metastasis. Helicobacter pylori (HP) induces EMT and thus causes gastric cancer (GC) by deregulating multiple signaling pathways involved in EMT. TWIST1 and MAML1 have been confirmed to be critical inducers of EMT via diverse signaling pathways such as Notch signaling. This study aimed to investigate for the first time possible associations between TWIST1 / MAML1 mRNA expression levels, HP infection, and clinicopathological characteristics in GC patients. Method: TWIST1 and MAML1 mRNA expression levels were evaluated in tumoral and adjacent normal tissues in 73 GC patients using the quantitative reverse transcription PCR (RT-qPCR) method. PCR technique was also applied to examine the infection with HP in GC samples. Results: Upregulation of TWIST1 and MAML1 expression was observed in 35 (48%) and 34 (46.6%) of 73 tumor samples, respectively. Co-overexpression of these genes was found in 26 of 73 (35.6%) tumor samples; meanwhile, there was a significant positive correlation between MAML1 and TWIST1 mRNA expression levels ( P  < 0.001). MAML1 overexpression exhibited meaningful associations with advanced tumor stages ( P  = 0.006) and nodal metastases ( P ˂ 0.001). 34 of 73 (46.6%) tumors tested positive for HP, and meanwhile, MAML1 expression was positively related with T ( P  = 0.05) and grade ( P  = 0.0001) in these HP-positive samples. Increased TWIST1 expression was correlated with patient sex ( P  = 0.035) and advanced tumor grade ( P  = 0.017) in HP-infected tumors. Furthermore, TWIST1 and MAML1 expression levels were inversely linked with histologic grade in HP-negative tumor samples ( P  = 0.021 and P  = 0.048, respectively). Conclusion: We propose TWIST1 and MAML1 as potential biomarkers of advanced-stage GC that determine the characteristics and aggressiveness of the disease. Based on accumulating evidence and our findings, they can be introduced as promising therapeutic targets to modify functional abnormalities in cells that promote GC progression. Moreover, HP may enhance GC growth and metastasis by disrupting TWIS1/MAML1 expression patterns and related pathways.